Synthesis and Characterization of Some Oxazepine Compounds from 2- Amino Thiazole - Zainab Muhsin Bdaiwi (Journal of Global Pharma Technology, 2020)
A chains of new heterocyclic oxazepin compounds contain thiazole ring were Produced via two steps, the first step comprising condensation of 2- amino thiazol and various aldehydes, (3- hydroxy benzaldhyede, 4- nitro benzaldhyede, 4- chloro benzaldhyede and 4-dimethylamino benzaldhyede), and second step formation oxazepin as sevene membred ring compounds, by cycloreaction of these Schiff bases and (pathalic, malic anhydride) in tolune as solvent. These compounds were established via melting point, FTIR, HNMR, C13NMR spactra. Keywords: 2 amino thiazol, oxazepin heterocyclic, Schiff base.